A cost-effectiveness evaluation of enamel matrix derivatives alone or in conjunction with regenerative devices in the treatment of periodontal intra-osseous defects - Listl, Stefan; Tu, Yu-Kang; Faggion Junior, Clóvis Mariano (Journal of clinical periodontology, 2010)
To identify the most cost-effective approach to treatment of infrabony lesions with enamel matrix derivatives (EMD).
Gesehen am 28.03.2023